Forage yield and crude protein content of lucerne cultivars established in the Ebro Middle Valley. Preliminary results - Andueza D.; Muñoz F.; Maisterra A.; Delgado I. (Quality in lucerne and medics for animal production, 2001)
A lucerne cultivar trial was carried out on an irrigated plot located in Zaragoza (Spain). Eighteen cultivars sown in a randomised block design with three replications were tested under four cuts in 1999. Dry matter (DM) yield and crude protein (CP) content were recorded at 10 per cent bloom for each replicate and cut. For DM yield, there were differences between cuts and cultivars. For CP content, the cultivar ¥ cut interaction was significant. This interaction could be due to the difference between cultivars for their tolerance to the fungus disease produced by Pseudopeziza medicaginis.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)